Son, sacrifice, and great shepherd: studies on the Epistle to the Hebrews - Moffitt, David M.; Mason, Eric Farrel (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
"Over the last few decades scholarly interest in the Epistle to the Hebrews has experienced something of a renaissace. Focusing on three major sections of the Epistle to the Hebrews (chapters 1-2, 8-10, and 13), the essays in this volume offer fresh and illuminating insights into some of the most puzzling aspects of this early Christian text." --back cover